Pengaruh Green Marketing dan Brand Image terhadap Minat Beli Konsumen Produk The Body Shop (Studi Kasus pada Konsumen Produk The Body Shop di Kecamatan Medan Sunggal) - Bangun, Agnes Mey Delita br; Syahputri, Yuni; Marbun, Patar (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Increasing public awareness of global warming issues has driven the cosmetic industry to implement sustainable marketing strategies. This study aims to analyze the influence of Green Marketing and Brand Image on Purchase Intention of The Body Shop consumers in Medan Sunggal District, both partially and simultaneously. This research employs a quantitative associative method. The population consists of The Body Shop consumers in the Medan Sunggal area, with a sample size of 96 respondents selected using Purposive Sampling technique. Data collection was conducted through questionnaires that had been tested for validity and reliability, then analyzed using Multiple Linear Regression via SPSS software. The results indicate that: (1) Green Marketing has a positive and significant effect on Purchase Intention (tvalue 3.552 > ttable 1.986); (2) Brand Image has a positive and significant effect on Purchase Intention and is the dominant variable influencing consumer decisions (tvalue 11.628 > ttable 1.986); (3) Simultaneously, Green Marketing and Brand Image have a significant effect on Purchase Intention (Fvalue 146.361 > Ftable 3.09). The ability of both independent variables to explain Purchase Intention is 75.4%, while the remaining variance is influenced by other factors outside the research model. The implications of this study emphasize the importance for companies to maintain a consistent ethical brand reputation to sustain consumer purchase intention.